Sistem Pendukung Keputusan Pemilihan Pemasok Batik Ruzza Menggunakan Metode Simple Additive Weighting (SAW) - Vidia Ruzza; Alamsyah Farizki Ramdhani; Farhan Adi Saputra; Citra Wiguna (JURIKOM (Jurnal Riset Komputer), 2022)
Batik Ruzza is a batik industry UMKM that was developed in the Pekalongan area, Central Java. The trademark "Batik Ruzza" has been producing batik clothes for more than 20 years. Batik Ruzza in carrying out its activities is very focused on raw materials, quality, completeness, and service. The problem with MSME Batik Ruzza is that there is a defect in the Batik Ruzza product which causes a buildup of clothing products that cannot be sold on the market. This is partly due to the non-optimal selection of raw material suppliers for batik clothes to improve the quality of Batik Ruzza products. The purpose of this research is to determine the right criteria for the company in determining the supplier of raw materials appropriately. The method used is Simple Additive Weighting (SAW). The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The selected criteria attributes are price, quality, completeness, delivery, and service. Based on the calculations carried out, it was found that the best supplier recommendation was the alternative A5 or Tiara which was worthy of being used as a supplier of batik cloth for Batik Ruzza clothing products